Reactivity against Sarcocystis neurona and Sarcocystis falcatula-like in horses from Southeastern and Midwestern Brazil - Silva, Thiago Merighi Vieira da [UNESP]; De Santi, Mariele [UNESP]; Gonçalves, Luiz Ricardo; Merino, Márcia Mariza Jusi; André, Marcos Rogério [UNESP]; Machado, Rosangela Zacarias [UNESP] (FapUNIFESP (SciELO), 2023)
Equine protozoal myeloencephalitis (EPM) is a neurological disease caused by Sarcocystis neurona. Immunofluorescence antibody tests (IFATs) have been widely used to identify exposure of horses to S. neurona in Brazil. Here we used IFAT to search for IgG antibodies against Sarcocystis falcatula-like (Dal-CG23) and S. neurona (SN138) in sera from 342 horses sampled in Campo Grande, Mato Grosso do Sul state (Midwestern), and São Paulo, São Paulo state (Southeastern), Brazil. The 1:25 cutoff value was chosen to maximize sensitivity of the test. IgG antibodies against S. neurona were detected in 239 horses (69.88%), whereas IgG antibodies against S. falcatula-like were detected in 177 horses (51.75%). Sera from 132 horses (38.59%) reacted against both isolates. Absence of reactivity was evidenced in 58/342 horses (16.95%). The lower cutoff used, and the presence of opossums infected with S. falcatula-like and Sarcocystis spp. in the regions where the horses were sampled, might justify the high seroprevalence observed here. Owing to the similarity among antigens targeted in immunoassays, reports on S. neurona-seropositive horses in Brazil may also derive from the exposure of horses to other Sarcocystis species. The role of other Sarcocystis species in causing neurological diseases in horses in Brazil remains unclear.